Symptoms of sexual dysfunction in men with chronic patient patial syndrome / chronic prostatit of III type and depression - M. N. Kryuchkova; A. Ya. Perechov (Вестник урологии, 2018)
Introduction. With CPPS / CP III, symptoms of sexual dysfunction and mental pathology are often simultaneously detected.Goal. Analysis of sexual dysfunction in patients with CPPS / CP IIIA, CPPS / CP IIIB and the existing affective pathology, comparing these groups of patients with CPAP / CP IIIA and IIIB with each other.Materials and methods. 65 men with type III CPAP / CP were examined, 41 patients were included, which comprised 2 comparison groups: 12 patients with CPPS / CP IIIA (group 1) and 29 patients with CPPS / CP IIIB - group 2. All patients did not have testosterone abnormalities, did not respond to standard urological therapy. Diagnosis of mental disorder and sexual dysfunction was established clinico-psychopathologically, the «International Index of Erectile Dysfunction» (ICEF) scale was applied; the severity of the pain was assessed using a visual analog scale (VAS). Statistical calculations were performed in the R Foundation for Statistical Computing, Vienna, Austria, version 3.2.Results. Patients of both groups were diagnosed with a primary depressive episode in the 1st comparison group - 75%, in the 2nd comparison group in 80%; depressive episode within the recurrent (recurrent) depressive disorder - in the 1 group 25%, in the 2 group 7%, in the bipolar affective disorder only in the 1 group - 7%; 1 obsessive-compulsive disorder (Table 1) was diagnosed in 1 patient (3%) in the 2nd group. In both groups, moderate episodes of moderate severity predominated-92% in group 1 and 62% in group 2; Depressive episodes of mild degree were 8% in 1 group and 28% in 2 comparison groups; A severe depressive episode was observed only in the 2nd comparison group at 7%. Erectile dysfunction was detected in 75% of patients in group 1, 93% in patients in group 2, premature ejaculation in group 1 in 58%, in group 2 in 45% of patients, reduction in libido in group 1 in 92%, in group 2 in 100%, pain during the ejaculation in group 1 was presented by 33%, in the 2nd group in 28% of men.Discussion and conclusions. Erectile dysfunction and decreased libido prevailed in patients of both comparison groups, were observed against the background of depressive episodes and, possibly, can be regarded as symptoms of disruption of vital functions within the atypical depressive syndrome of depressive disorders in both groups. ED, decreased libido (sexual desire, desire and attraction), premature ejaculation, general dissatisfaction with sexual intercourse were observed in both groups of patients with CPPS / CP III against a background of depressive episodes, comparing the frequency of occurrence of symptoms of sexual dysfunction does not reveal significant differences in the compared groups. It is advisable to further study the symptoms of sexual dysfunction in CPPS / CP III and psychopathology, their development in the length of the disease, and the relationship for the development of comprehensive CPPS / CP III therapy.